PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENGEMBANGAN MODEL DESA KONSERVASI DAN EKOWISATA DI KAWASAN TAMAN NASIONAL MERU BETIRI - Hari Rujito (UNEJ e-Proceeding)
This study aims to (i) assess the effectiveness of the development of Model Villages Conservation (MDK) and ecotourism in the area around the national park which is a strategy of economic empowerment in the region TNMB and (ii) to compile a "Road Map" that correspond to the development of community empowerment in each village conservation and ecotourism in the area TNMB. The method used is a method of quantitative and qualitative methods TEV PRA (Participatory Rural Appraisal). The location of research is in the area of Meru Betiri which includes three (3) sections: Section Area I Sarongan (Rajegwesi), Section Ambulu Region II and Region III Section Rajegwesi and Kalibaru (Kebunrejo). The results showed the achievement of community development activities in Banyuwangi TNMB is pretty good, whereas in the region for achieving results TNMB Jember mediocre and still needs to be improved.